Refining the Architecture Recovery Approach ArchMine by Incrementally Performing Evaluation Studies - Vasconcelos, Aline; Werner, Cláudia (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2008)
Several architecture recovery approaches have been proposed in the literature with distinct goals. ArchMine, an architecture recovery approach based on dynamic analysis and data mining, aims to assist in program understanding and software reuse by detecting cohesive classes that implement a set of related functionalities, i.e. architectural elements. It is supported by a tool set integrated into a reuse based software development environment. The approach and its tool set have been detailed in previous works. The focus of this paper is to describe how ArchMine and its tool set were evaluated and refined through a series of evaluation studies. These evaluations allowed to gradually refine the approach based on the lessons learned.